Analisis Perencanaan Persediaan Untuk Meningkatkan Pengendalian Biaya Produksi Pada Mebel Tenang Jaya - Devi Lestari Pramita Putri; Citra Larashati Surya (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2020)
FAbstract - Furniture Tenang Jaya Is a business that is engaged in furniture. The raw material used is teak wood, in a smooth production process, the company must provide sufficient raw material so that they do not experience excess or lack of raw material. The research method used is descriptive quantitative data in the form of numbers, Data collection techniques used were interviews and documentation. Data analysis techniques used in this study are by step (1) Production data (2) Determine Lead time (3) Determine Safety Stock (4) Determine Re-order Point (5) Calculated the most economical amount of goods purchased using the Economic Method Order Quantity (6) Determine Total Cost (7) Determine maximum Stock Maximum Stock (8) Determine Order Frequency (9) Make a graphic image / curve to measure Safety Stock, Reorder Point (ROP), and Economic Order Quantity (EOQ) positions so the results of the analysis are clear. The result showed that in 2017 Lead Time was IDR 16.159.500. Safety Stock is IDR 17.955.000. Re-order Points as much as IDR 34.114.500. Economic Order Quantity 3.870. The booking IDR 9.250.000 and the storage IDR 7.770.000. IDR 17.958.870. maximal stock the order frequency is 5 times. In 2018 the lead time was Idr 19.563.600 Safety Stock was IDR 23.273.997. Re-orde Points as much as IDR 42.927.597. Economic Order Quantity 4.152 The booking Rp 10.000.000 and the storage Rp. 10.200.000. Maximal stock of IDR 23.278.149 The order frequency is 5 imes. By using the economic order quantity method in Tenang Jaya Furniture, it can streamline production costs. Keyword: Inventory Planning, Controlling Production Cost